2016
DOI: 10.3168/jds.2015-10389
|View full text |Cite
|
Sign up to set email alerts
|

Description and evaluation of a net energy intake model as a function of dietary chewing index

Abstract: Previously, a linear relationship has been found between net energy intake (NEI) and dietary chewing index (CI) of the diet for different types of cattle. Therefore, we propose to generalize and calibrate this relationship into a new model for direct prediction of NEI by dairy cows from CI values (CI; min/MJ of NE). Furthermore, we studied the forage-to-concentrate substitution rate in this new NEI model. To calibrate the model on a diverse set of situations, we built a database of mean intake from 14 producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
2
6
1
Order By: Relevance
“…The exact mechanism behind how cows substitute intake among concentrate and forage or PMR is unknown (Jensen et al, 2016 substitution rate when dairy cows were fed concentrate separately from forage found that feeding a high-starch concentrate had a higher substitution rate compared with a high-fiber concentrate (Faverdin et al, 1991), which contrasts with the results observed in the current study. However, it is important to note that Faverdin et al (1991) did not feed concentrate alongside a PMR but rather concentrate separate to silage only, and the amount of concentrate accounted for up to 50% of total DMI.…”
Section: High-starch Vs High-fiber Pelletcontrasting
confidence: 99%
“…The exact mechanism behind how cows substitute intake among concentrate and forage or PMR is unknown (Jensen et al, 2016 substitution rate when dairy cows were fed concentrate separately from forage found that feeding a high-starch concentrate had a higher substitution rate compared with a high-fiber concentrate (Faverdin et al, 1991), which contrasts with the results observed in the current study. However, it is important to note that Faverdin et al (1991) did not feed concentrate alongside a PMR but rather concentrate separate to silage only, and the amount of concentrate accounted for up to 50% of total DMI.…”
Section: High-starch Vs High-fiber Pelletcontrasting
confidence: 99%
“…Chewing time of feeds, or chewing index (CI; min/kg of DM), is highly variable. Jensen et al (2016) reported for 80 diets that CI of TMR averaged 35.1, ranging from 24.6 to 62.5, whereas CI of diets with separate ingredient feeding averaged 38.2, ranging from 30.2 to 49.4. In the meta-analysis of Zebeli et al (2006), CI ranged from 17.9 to 47.1 (n = 99), with a mean of 30.1.…”
Section: Predicting Chewing Timementioning
confidence: 99%
“…Hence, the correlation between eating and ruminating time for dairy cows was relatively low when examined across studies (e.g., r = 0.27, P < 0.05; White et al, 2017). Maximum total chewing time for dairy cows is estimated at about 16 h/d (Zebeli et al, 2006;Jensen et al, 2016;White et al, 2017).…”
Section: Complementarity Between Eating and Ruminating Timementioning
confidence: 99%
“…The chewing index, expressed as minutes of chewing elicited per kilogram of DM, typically decreases as forage NDF digestibility increases, particle length is shortened, or NDF content decreases. A negative linear relationship exists between DMI and the dietary chewing index for silage-based diets primarily composed of grass and grass-clover silages, alfalfa silage, corn silage, and whole-crop silages (Jensen et al, 2016). Although not reflected in the chewing index, part of the potentially negative effect of some silages on energy intake is related to low silage DM content and the negative effects of higher silage fermentation end products (Huhtanen et al, 2007).…”
Section: Silage Fiber Characteristics Feeding Behavior and Dmimentioning
confidence: 99%